(untitled) (AYUSHDHARA, 2025)
Uterine fibroids are fibrous growth in myometrium of the uterus also known as leiomyomas are increasing, prevalence in reproductive age is 20 to 50% and 30% in perimenopausal age. Leiomyomas, are benign smooth muscle neoplasms most of the time are asymptomatic and are found out during routine examination, some show complaints like pain, pressure sensations, dysmenorrhea or abnormal uterine bleeding. Conventional Management of uterine fibroid includes oral contraceptives, hormonal injections or IUD and surgery to meet urgent need of the patient, but challenges remain to establish a satisfactory conservatory medical treatment till date. As standard treatment gives Symptomatic relief and has recurrence if medicine discontinued, Whereas Ayurveda has a holistic approach in treatment and restores balance naturally. The following case report proffers the management of a female diagnosed with uterine fibroids. In this case a 45-year-old woman visited clinic with complaints of bleeding p/ v for two months and lower back ache. The case report illustrates the before and after reports, after taking 2 months treatment at Jeena Sikho life care limited Hospital, Kanpur, Uttar Pradesh.